2020
DOI: 10.1177/0267659120948427
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of healthcare-associated infections in patients with fever during the first 48 hours after decannulation from veno-venous extracorporeal membrane oxygenation

Abstract: Introduction: Fevers following decannulation from veno-venous extracorporeal membrane oxygenation often trigger an infectious workup; however, the yield of this workup is unknown. We investigated the incidence of post-veno-venous extracorporeal membrane oxygenation decannulation fever as well as the incidence and nature of healthcare-associated infections in this population within 48 hours of decannulation. Methods: All patients treated with veno-venous extracorporeal membrane oxygenation for acute respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…On the other hand, the presence of bacterial biofilm on the cannulas' surfaces cannot be excluded, even in patients without proven bacteriemia [17,18]. The critical time for the development of inflammatory response is shown to be 48 h [19]. However, the risk factors for the development of the post-decannulation SHI phenomenon remained undetermined [20].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…On the other hand, the presence of bacterial biofilm on the cannulas' surfaces cannot be excluded, even in patients without proven bacteriemia [17,18]. The critical time for the development of inflammatory response is shown to be 48 h [19]. However, the risk factors for the development of the post-decannulation SHI phenomenon remained undetermined [20].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…A study analysing the rates of cannula colonisation and infection using cannula, blood and skin swab cultures after ECMO removal showed a 33% rate of colonisation and a 9% rate of infection [21]. Interestingly, none of the patients presented with infection signs at decannulation or during the following 48 h, and the culture positivity in patients who develop fever after removal of ECMO support remains low [22 ▪ ]. Regarding colonisation of other parts of the circuit, a recent retrospective study in 112 patients revealed a 11.6% rate of oxygenator colonisation, which was significantly associated lower survival (23.1% vs. 76.8% in the noncolonised group) [23 ▪ ].…”
Section: Epidemiology and Outcomesmentioning
confidence: 99%